Application of solute distribution theory to melt crystallization of fatty acids. (2nd April 2016) - Fukui, Keisuke; Fujikawa, Takuto; Satone, Hiroshi; Yamamoto, Takuji; Maeda, Kouji; Kuramochi, Hidetoshi
Abstract: To study solute distribution at the solid–liquid (S–L) interface during melt crystallization, we examined the applicability of the interfacial solute distribution factor proposed based on a kinetic model involving both mass and heat balances at the interface. The factor derived from the model was compared with the experimental results obtained by employing a binary melt with the different species and concentrations of fatty acids as biodiesel related mixtures. As a result, we were able to reveal the empirical relation between the purity of the crystal and the solidification conditions of the melt. Based on the model, we also numerically calculated the transient changes in the interfacial solute distribution factor as well as the temperature of the S–L interface in the solidification process of the melt. The minimization of the factor was confirmed when the melt was supercooled at the S–L interface after starting solidification. Highlights: Melt crystallization of fatty acids as biodiesel related mixtures. Solute distribution at the solid–liquid (S–L) interface. Interfacial solute distribution factor. Relationship between the purity of the crystal and the solidification conditions. Numerical calculation of the interfacial solute distribution factor.